2007
DOI: 10.1371/journal.pone.0000429
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Mouse Urine Volatiles: In Search of MHC-Dependent Differences

Abstract: Genes of the major histocompatibility complex (MHC), which play a critical role in immune recognition, influence mating preference and other social behaviors in mice. Training experiments using urine scent from mice differing only in the MHC complex, from MHC class I mutants or from knock-out mice lacking functional MHC class I molecules (ß2m-deficient), suggest that these behavioral effects are mediated by differences in MHC-dependent volatile components. In search for the physical basis of these behavioral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
(52 reference statements)
3
17
0
Order By: Relevance
“…The picture on the variability of urinary peptides emerging from this study is very similar to that described for urinary volatiles 16 . In natural wild populations, urinary peptide patterns will differ qualitatively and quantitatively between individuals.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The picture on the variability of urinary peptides emerging from this study is very similar to that described for urinary volatiles 16 . In natural wild populations, urinary peptide patterns will differ qualitatively and quantitatively between individuals.…”
Section: Discussionsupporting
confidence: 76%
“…However, no qualitative and only negligible quantitative variations in a large number of different volatiles have been observed when comparing urine mixtures of groups of an inbred wild-type strain and a congenic knock-out strain lacking functional MHC class I molecules. In contrast, more quantitative differences were observed between groups of the same inbred wild-type strain derived from different breeders 16 (for a review, see Kwak et al 17 ). Hence, whereas variability in small airborne organic molecules may be important for recognition of individual scent owners 18,19 , physical evidence for an influence of the MHC on urinary volatiles remains elusive.…”
mentioning
confidence: 99%
“…Given that MHC and ESP regions exhibited strong linkage in our mice, this also implies that mice did not use Esp genes as a marker for kin recognition either. To date, there is no convincing evidence from mouse studies that MHC is used as a genetic kinship marker among genetically heterogeneous animals, or that MHC can provide a consistent kinship signature that is recognizable across different genetic backgrounds [24,39,[56][57][58][59], in strong contrast to recognition of MUP type.…”
Section: Discussionmentioning
confidence: 99%
“…SDS-PAGE analysis confirmed that CD-1 strain males express normal adult male levels of darcin, though a little lower than that typical of wild or C57BL/6 strain males at approximately 8% of total urinary MUP output (Figure 2E ). By contrast, BALB/c males express extremely low levels of the darcin pheromone (<0.5% of total MUP output, Roberts et al, 2010 , Figure 2E ), although they have normal expression of other known male-specific pheromones (Willse et al, 2006 ; Röck et al, 2007 ; Haga et al, 2010 ). Urine from singly housed BALB/c males failed to stimulate a significant increase in neurogenesis (Figure 2Ac ).…”
Section: Resultsmentioning
confidence: 99%